Antimicrobial activity of the essential oil of Cymbopogon citratus (DC) Stapf. on Staphylococcus spp., Streptococcus mutans and Candida spp. - RBA Almeida; G Akisue; LML Cardoso; JC Junqueira; AO C Jorge (Universidade Estadual Paulista, 2013)
Medicinal plants with fungicide action, antibacterial and anti-inflammatory effects are under investigation. The main purpose of this work was to evaluate the antimicrobial activity of the essential oil from Cymbopogon citratus (DC) Stapf. on strains of Staphylococcus spp., Streptococcus mutans and Candida spp. with planktonic and biofilm growth. To study the micro-organisms in planktonic cells, the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were determined by using 9 clinical strains for each species and 1 ATCC (American Type Culture Collection) from C. albicans, C. tropicalis, C. glabrata, S. aureus, S. epidermidis and S. mutans. In order to evaluate the effects of the essential oils on biofilms, strains of S. aureus (ATCC 6538), S. mutans (ATCC 35688) and C. albicans (ATCC 18804) were used. The biofilm was formed on acrylic resin discs with isolated micro-organisms or in associations. The number of colony-forming-units (CFU) obtained in each biofilm (CFU/ml) was submitted to Student's t statistical test. The results demonstrated that the essential oil of Cymbopogon citratus showed microbiostatic and microbicidal activity against all tested strains. The average CFU/ml for the biofilm of S. aureus, S. mutans and C. albicans, whether isolated or in association, was lower in the group treated with essential oil than in the control group.